The Enhancement of Prisoner’s Family Adaptation through Assimilative Integration Family Counseling Based on Structural Family Counseling Theory - Pramaulsuk, Yongyuth; Kulnapadol, Pennapha; Inang, Pracha (Journal of The Royal Thai Army Nurses, 2020)
The purpose of this research was to study the component of family adaptation and develop format of family adaptation. It was divided into 2 steps. The first step studied confirmed element of family adaptation and the second step was family counseling to enhance family adaptation. The samples were wife and son or daughter of prisoner who was imprisoned less than 1 year with the lowest family adaptation scores. Twenty families were performed simple random sampling into the experimental and control group. The instruments were family adaptation measurement and 10 sessions of assimilative integration family counseling based on structural family counseling theory which developed by the researcher. The confirmatory factor analyses, the multivariate analysis of variance with repeated measures were used for analyzing the data. The results revealed that 1) The component of family adaptation were family function, family relationship, social relationship, and readiness to solve problem. 2) The mean score of family of the experimental group after intervention and after 4 months was higher than those in the control group statistically significant different at .05 level.